Determination of colistin in luminal and parietal intestinal matrices of chicken by ultra‐high‐performance liquid chromatography‐tandem mass spectrometry. Issue 6 (6th October 2021) - Mead, Andrew; Gillard, Nathalie; Robert, Christelle; Pierret, Gilles; Henrottin, Jean; Richez, Pascal; Pelligand, Ludovic
Abstract: Justification for continued use of colistin in veterinary medicine, for example medicated water, relies on pharmacokinetic/pharmacodynamic (PK/PD) studies that require accurate measurement of colistin content in the digestive tract. A method for the detection and quantification of colistin in poultry intestinal material was developed and validated. Colistin is not absorbed after oral administration, and the biophase is the gastrointestinal tract. Extraction of colistin from the matrix was achieved using solid‐phase extraction with a methanol:water (1:2; v/v) solution. Polymyxin B was used as an internal standard. Colistin A and colistin B, the main components of colistin, were separated, detected and measured using ultra‐high‐performance liquid chromatography coupled with tandem mass spectrometry (UHPLC‐MS/MS). The method was validated for linearity/quadraticity between 1.1 (LOQ) and 56.7 mg/kg. Mean accuracy was between 82.7% and 107.7% with inter‐ and intra‐day precision lower than 13.3% and 15% respectively. Freeze–thaw, long‐term and bench storage were validated. Incurred samples following colistin treatment in poultry at the approved clinical dose of 75, 000 IU/kg in drinking water and oral gavage were quantifiable and in line with expected intestinal transit times. The method is considered appropriately accurate and precise for the purposes of pharmacokinetic analysis in the gastrointestinal tract.